A benchmark for validation of numerical results in sheet metal forming - Santos, Abel D. (2004)
Advances in FE codes for simulation of sheet metal forming processes have enabled its use during pre-production stage of a component. Some of recent developments include improvements and implementation of new material models of mechanical behaviour. However, these developments and corresponding results need to be validated, which means being compared with experimental results. On the other hand, in order that experimental results are a reference data, they need to be tested to repeatability and need to be obtained with such characteristic preferably by different institutions.